A preliminary exploration of how Sarawak indigenous popular music contributes to the development of Sarawakian identity. - Collin, Jerome; Ting, Su Hie; Esther John, Perry; Connie Lim, Keh Nie (Asian Journal of Research in Education and Social Sciences, 2023)
This study aimed to investigate the role of Sarawak indigenous popular music (SIPM) in shaping the identity of Sarawakians at personal, social, local, and regional levels. Using surveys and interviews, the research examined how SIPM was perceived by Sarawakians and how it contributed to the creation of their unique identity. The findings revealed that respondents identified SIPM as music that is sung or performed in Sarawak indigenous languages, incorporates musical elements of ethnic groups in Sarawak, portrays indigenous lifestyles and cultures, and represents identities of indigenous groups in Sarawak. The study also found that SIPM played a significant role in creating the Sarawakian identity, which symbolizes the state’s diversity, distinctiveness, and harmony through its lyrics, rhythm, beat, and musical activities or engagements it generated. The study’s implications suggest that indigenous popular music has a more extensive impact on shaping people’s identity beyond their indigenous consciousness. Further research could build on these findings to examine the potential of indigenous popular music in constructing a sense of identity among diverse communities across the world.